An integrative ethical approach to leader favoritism. Issue 1 (20th July 2020) - Yang, Inju; Horak, Sven; Kakabadse, Nada K.
Abstract: Relationship building is one of the most important aspects of leadership; however, it can pose ethical challenges. Though particularistic treatment of employees by leaders, that is, leader favoritism, commonly occurs, it is conventionally regarded negatively as fairness norms require leaders to treat followers equally. In this conceptual study, we explore different views on leader favoritism based on different ethical principles. We develop an alternative to the conventional view and suggest that leader favoritism may not necessarily lead to negative outcomes when empathy‐based favoritism is applied. In this vein, we recommend drawing on the ethical principles of a utilitarian approach by balancing particularism and universalism, which is also helpful to build organizational social capital. We contribute to leadership theory by developing an early concept of an integrative ethical approach to leader favoritism.